Farm water: too little and too much: a tale from two islands - Chan Soo, Rhonda (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
In this his/her story (HHS), we hear from two farmers from the IICA-CBF (Caribbean Biodiversity Fund) EbA (ecosystem-based adaptation) Project’s Farmers’ Caucus, Neil Gomes from Antigua and Barbuda, and Shennelle Herbert from Trinidad and Tobago, to learn about their experiences navigating increased climate risks, amidst other challenges, how they are innovating, and the interventions they will access through the project.